2015
DOI: 10.1093/mnras/stv1656
|View full text |Cite
|
Sign up to set email alerts
|

On the red-giant luminosity bump

Abstract: The increase in luminosity as a star evolves on the red-giant branch is interrupted briefly when the hydrogen-burning shell reaches the vicinity of the composition discontinuity left behind from the first convective dredge-up. The non-monotonic variation of luminosity causes an accumulation of stars, known as the 'bump', in the distribution of stars in the colour-magnitude diagrams of stellar clusters, which has substantial diagnostic potential. Here I present numerical results on this behaviour and discuss th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…The star regains a pivot when the hydrogen-burning shell reaches the mean molecular weight discontinuity. In line with Christensen-Dalsgaard (2015), who has already shown that the encounter of the hydrogen-burning shell with the mean molecular weight discontinuity coincides with the luminosity minimum of the bump.…”
Section: Discussionsupporting
confidence: 87%
“…The star regains a pivot when the hydrogen-burning shell reaches the mean molecular weight discontinuity. In line with Christensen-Dalsgaard (2015), who has already shown that the encounter of the hydrogen-burning shell with the mean molecular weight discontinuity coincides with the luminosity minimum of the bump.…”
Section: Discussionsupporting
confidence: 87%
“…The same phenomenon is responsible for the occurrence of the luminosity bump in red-giant stars (e.g. Thomas 1967;Christensen-Dalsgaard 2015), first discussed in the context of temporary Roche-lobe detachment in LMXBs in Tauris & Savonije (1999). The interruption of the mass transfer can be a temporary effect if the envelope is massive enough, such that when the burning shell has passed through the discontinuity, the star still has enough material to burn and can therefore resume its mass transfer.…”
Section: Effect Of Metallicitymentioning
confidence: 85%
“…In fact, the situation is more complex with the luminosity beginning to decrease prior to the shell burning through the discontinuity. As discussed by Christensen-Dalsgaard (2015) the reason is that the decrease in µ above the discontinuity starts affecting the hydrostatic structure, and hence the temperature, within and above the hydrogenburning shell before it reaches the discontinuity. This causes the decrease in the luminosity.…”
Section: Hydrogen Shell Burning Phase: Subgiants and Red-giant Branchmentioning
confidence: 99%